Thermal Performance Characteristics of a Microchannel Gas Heater for Solar Heating Applications - Bo Yang (MDPI AG, 2021)
In the present article, the heat transfer and fluid flow of the air in a compact microchannel gas heater (MCGH) was experimentally quantified. To understand the effect of heat flux value (HFV), and inlet velocity on the heat transfer coefficient (HTC), wall temperature, friction factor, Nusselt number, average pressure-drop value (PDV) and performance index (PI), a microchannel gas heater was constructed and tested with pressurized air. The results showed that the HTC was 20 W/(sqmK) to 70 W/(sqmK), corresponding to inlet velocities 6.7 m/s and 16.7 m/s, respectively within HFV < 1 kW/m2. Also, the highest PI was 1.19 meaning that the HT rate can be increased by 19% at u = 15 m/s in comparison with the reference case (at u = 13.3 m/s). Likewise, the HTC was intensified once the inlet velocity is increased. It was also identified that increasing the HFV has a strong effect on wall temperature, however, slightly changes the HTC. By increasing the heat flux value from 200 W/sqm to 1000 W/sqm, the HTC increased only by 4.7% which was associated with the poor thermophysical properties of air flowing inside MCGH. Two main mechanisms of wall slip and viscous heating were identified as main contributors to the heat transfer enhancement in MCGH.